Keberterimaan Media Multimodalitas Berbasis Website Pada Materi Pubertas di Sekolah Dasar: Tinjauan The 2nd Unified Theory of Accepptance and Use of Technology (UTAUT) Model - Rofita Rahayu; Yunus Abidin; Dede Trie Kurniawan (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The research aims to identify the dominant factors influencing the acceptance of web-based multimodal learning media in elementary schools. The research method employed is a quantitative survey using variables within the 2nd UTAUT model. The research sample consists of 100 elementary school teachers, selected through random sampling techniques. The research instrument uses a Likert scale questionnaire. Data analysis is conducted using the SmartPLS 4.0 application. Based on the research findings, it is evident that there are factors that have a significant impact on the acceptance of web-based multimodal learning media. These factors include User Habit (IUH) and Social Influence (SI). Behavioral Intention (BI), it is influenced by Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facility Condition (FC), User Habit (IUH), Perceived Learning Opportunity (PLO), and Hedonic Motivation (HM), which have a positive but non-significant influence. In conclusion, teachers' intention to utilize web-based multimodal learning media is strongly supported by their familiarity with technology (IUH) and social influence (SI), which motivates them to develop and use available learning media.